Dragon of the red dawn - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2007)
When Merlin is weighed down by sorrows, Jack and Annie travel back to feudal Japan to learn one of the four secrets of happiness.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Happiness -- Juvenile fiction; Tree houses -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Time travel -- Fiction; Magic -- Fiction; Happiness -- Fiction; Tree houses -- Fiction; Brothers and sisters -- Fiction; Historical fiction; Japan -- History -- Tokugawa period, 1600-1868 -- Juvenile fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Japan -- History -- Tokugawa period, 1600-1868 -- Fiction; Historical fiction